Autophagy in sexual plant reproduction as an emerging field - Zhao, Peng (Plant Signal Behav, 2015)
Autophagy is an evolutionary conserved system for clearing and recycling cellular components. Critical roles of autophagy in the responses of plant to different environmental stresses have been revealed during past decades. However, little is known about the role of autophagy in plant developmental processes, especially in the processes of sexual plant reproduction. Here, we briefly discuss recent advances in the emerging field and wish to bring some potential research directions into attention. Possible divergence of molecular mechanism of autophagy in respect to the current debatable view is also discussed.